McCloskey's Rhetoric - Balak, Benjamin (Routledge INEM Advances in Economic Methodology, 2006)
The rhetoric of economics has long claimed scientific objectivity, however the late, great economist Joan Robinson argued that 'the purpose of studying economics is not to acquire a set of ready-made answers to economic questions, but to learn how to avoid being deceived by economists.' This unique book examines the use of rhetoric in economics, focusing on the work of Deirdre McCloskey and other major economic philosophers. McCloskey is one of the most recognizable names in economics, yet this is the first real attempt to analyze her work in book form. She views economics as a language that uses all the rhetorical devices of everyday conversation, and her controversial standpoint on judging economics by aesthetic and literary standards has been hugely influential. Utilizing the views of Derrida and Foucualt amongst others, Benjamin Balak analyzes McCloskey's major texts and critically evaluates the linguistic, literary and philosophical approaches they introduce. This long overdue examination of the methodological and philosophical consequences of McCloskey's work will be of interest to philosophers and economists alike.